Descargas de aguas residuales y su incidncia en la calidad del agua de la microcuenca del río Daule, Cantón Pichincha. Año 2013. Plan de descontaminación - Suárez Nuñez, Yandri Fernando (2015)
This research has as its theme: "Wastewater discharge and its impact on water quality of the river Daule, canton Pichincha. Year 2013. Decontamination Plan". The methodology used was the literature study and field work, the instrument that allowed us to gather the information was a survey, observation and analysis of wastewater samples and laboratory analysis of water quality index Ephemeroptera, Plecoptera and Trichoptera( EPT ) . In view of the problems generated direct discharge Daule River in Canton Pichincha wastewater. We proceeded to the collection of information and analysis of wastewater. Same which are discharged directly to the river without giving Daule pretreatment yield as a result of this investigation that there is a high rate of pollution Daule River. As a solution to the problem, a review of bibliographic information, a decontamination plan raised the river through the construction of two treatment plants formed by a grit chamber, equalization or the primary settler, the UASB tank, dried bed and disinfection tank for each plant. In order that the sewage reaching the TULSMA allowable limits before discharge to the river Daule